2021
DOI: 10.1177/20416695211027920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Masks Worn to Protect Against COVID-19 on the Perception of Facial Attractiveness

Abstract: Wearing a sanitary mask tended, in the main, to reduce the wearer’s sense of perceived facial attractiveness before the COVID-19 epidemic. This phenomenon, termed the sanitary-mask effect, was explained using a two-factor model involving the occlusion of cues used for the judgment of attractiveness and unhealthiness priming (e.g., presumed illness). However, these data were collected during the pre-COVID-19 period. Thus, in this study, we examined whether the COVID-19 epidemic changed the perceived attractiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
55
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 28 publications
13
55
7
2
Order By: Relevance
“…Collectively, our first two studies, which show that face masks will help and never hinder one's perceived attractiveness conflicts with the findings of Miyazaki and Kawahara ( 2016 ) who showed that facial mask decrease the perceived attractiveness in a pre-COVID-19 pandemic era. Interestingly, the same lab has tested the same question recently during the pandemic and reported a similar result to our first two studies—attractiveness of below-average faces increased (Kamatani et al, 2021 ). A similar pattern of improvement in attractiveness ratings of unattractive faces is confirmed in another post-pandemic study (Patel et al, 2020 ), signifying the change in attitudes in response to social norms associated with mask wearing (Carbon, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Collectively, our first two studies, which show that face masks will help and never hinder one's perceived attractiveness conflicts with the findings of Miyazaki and Kawahara ( 2016 ) who showed that facial mask decrease the perceived attractiveness in a pre-COVID-19 pandemic era. Interestingly, the same lab has tested the same question recently during the pandemic and reported a similar result to our first two studies—attractiveness of below-average faces increased (Kamatani et al, 2021 ). A similar pattern of improvement in attractiveness ratings of unattractive faces is confirmed in another post-pandemic study (Patel et al, 2020 ), signifying the change in attitudes in response to social norms associated with mask wearing (Carbon, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…A similar pattern of improvement in attractiveness ratings of unattractive faces is confirmed in another post-pandemic study (Patel et al, 2020 ), signifying the change in attitudes in response to social norms associated with mask wearing (Carbon, 2021 ). However, the results of Kamatani et al ( 2021 ) for masked faces of above-average attractiveness showed a reduction in perception of attractiveness compared to unmasked faces—a result not found in the studies here and those of Patel et al ( 2020 ). Such discrepancy might be a result of cultural differences (Japanese vs. Western) or due to differences in the stimuli used, in terms of their range of attractiveness.…”
Section: Discussioncontrasting
confidence: 84%
“…Low-trustworthy faces were rated higher in trustworthiness when the face was covered by face masks as compared to the full face (Marini et al, 2021). For attractiveness, one study showed that masked faces appeared more attractive and healthier than full faces (Kamatani et al, 2021). Incidentally, masked faces could be approachable because they appear healthy looking.…”
Section: The Impact Of Face Masks On Social Interactionmentioning
confidence: 99%
“…The same research group replicated the procedures of the 2016 study in 2020, during the height of the COVID-19 pandemic in Japan, where virtually the entire population had taken to regularly wearing mask ( Kamatani et al, 2021 ). They hypothesized that this normalization of mask wearing would reduce the “unhealthiness priming” effect, since masks no longer held a signal regarding any individual’s personal health status and they had become a symbol representing conformity to societal norms ( Nakayachi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we follow the paradigm and logic developed by Miyazaki and Kawahara (2016) and Kamatani et al (2021) to study how a protective mask affects the attractiveness of the mask wearer during the height of the COVID-19 pandemic in North America. Our study design allowed us to test two hypotheses.…”
Section: Introductionmentioning
confidence: 99%